An Observational Study to Correlate Uterine Fibroid with Vyadhi in Ayurveda: Life Sciences-Ayurveda for Better Holisitc Therapy - Dr. Rajni K. Gurmule; Dr. GopalSharma; Dr. Priti Desai (International Journal of Life Science and Pharma Research, 2022)
Uterine fibroid is the common type of benign tumor of uterus which affects the health of women. These are mostly asymptomatic but still cause major morbidity in women. Along with menorrhagia, dysmenorrhoea fibroid also shows symptoms such as infertility, pain in lower abdomen, anemia due to blood loss. Hormonal therapy and symptomatic treatment are carried out to treat this disease. . In some advance cases, surgery is carried out. But there is no absolute treatment for cure of uterine fibroid till today. There is a description of various Ayurvedic diseases affecting the health of women. There is somewhat resemblance between Vyadhis in Ayurveda and uterine fibroid such as RaktajaGulma, Granthi and Arbuda. But there is an evidence gap regarding correlation of uterine fibroid with disease mentioned in Ayurveda. So we have made sincere effects to correlate Ayurvedic disease with uterine fibroid with the help of an observational study. Our study will aid to treat uterine fibroid using Ayurvedic principles. For this observational , study 30 womenof the age group 30-60 having uterine fibroid after takingtheir prior consent were taken by considering inclusion and exclusion criteria. Their USG reports of abdomen and pelvis were collected. Detailed clinical examination was carried out and case report formsfilled. After hysterectomy, gross examination of fibroid was carried out and their histopathology reports were collected for further study. We found mean age of occurrence of fibroid was40.4 years.Mean of symptoms to be visible was 22.44. Avednam, Snigdha, Na-Anyavearnam, Ashmopam, Apakam,AprachalyamaLakshana was found in 80%, 90%, 100%, 66.66%, 93%, 63.33% respectively From all the observation and results, at the end of this study, we concluded that uterine fibroid can be correlated with Arbuda and its subtype Mansarbuda.